Dinamika Peradaban Islam Pada Masa Tiga Dinasti Besar - Muh. Ilham; Wahid, Khaerunnisa (Jurnal Publisitas, 2023)
This study aims to analyze the main problems of the Ottoman Empire, the Safavid Empire of Persia, and the Mughal Empire of India. The problems studied are: How is the history of the Ottoman Empire, the history of the Safavid Empire of Persia, the history of the Mughal Empire of India? The research method used is qualitative research with library study data collection techniques. The data sources used are by reviewing, searching, and collecting information from several library sources as references, namely journals, articles, papers, and websites, which are related to this discussion. The results of this discussion explain that the peak of the glory of the Ottoman Empire in expanding the expansion area was the power of Sultan Sulaiman I (1520-1566), who was popularly known as Sulaiman the Great and Sulaiman Al-Qanun. The Period of Progress During the Safavid Empire’s rule in Persia (Iran) in the 16th and 17th centuries AD, the period of progress was only found in the reign of two Sultans, namely Ismail I (1501-1524 AD) and its glory during the reign of Sultan Syah Abbas I (1558-1622 AD). The peak of its glory was found in Sultan Mahmud Al-Ghaznawi, who led the conquest of India at the end of the 9th century and succeeded in controlling all of India and ruled there until 1186 AD.